Two-stage stochastic programming for urban water resources management - Luo, Kun. (2011)
Stochastic programming is one optimization approach applicable to the resource allocation problem, one of the classical problems in operations research. Decisions need to be made periodically over time for many water resources management problems. These problems can be formulated as two-stage stochastic programming (TSP) models. Conventionally, TSP was adopted mostly for agricultural water allocation problems.In this project, its applicability will be put in test for urban water resources management problems. With rapid urbanization in the last 50 years around the world, water shortage became increasingly pressing. It is a critical issue as water has been an essential element for both industrial development and domestic usage. This project serves as an interesting scientific inquiry as well as a valuable exploration of solution to this problem.